Reviving the Ancient Art of Making Persian Crucible Steel for Bladed Weaponry - Manouchehr Moshtagh Khorasani (Universidad de León, 2012)
This article is intended to both explain three traditional methods of manufacturing Persian crucible steel and to describe recent attempts by three German bladesmiths to replicate the results of traditional crucible steel making. The article will explain the process of making crucible steel, from the making of crucible steel cakes and forging of crucible cakes into bars, to polishing and etching these bars to reveal the crucible steel pattern. First described are three traditional methods of making crucible steel that are mentioned in Persian manuscripts. Second, elaborations are provided on three different modern processes carried out by three different talented German smiths, Achim Wirtz, Andreas Schweikert, and Cyrus Haghjoo. Finally, illustrations are shown some finished crucible steel blades made by Achim Wirtz and Andreas Schweikert as well as some crucible steel knives, made by the talented Belgian knifemaker Salsi Alessio, made from crucible steel bars provided by Achim Wirtz.